2019
DOI: 10.1111/pai.13111
|View full text |Cite
|
Sign up to set email alerts
|

Setting definitions of childhood asthma in epidemiologic studies

Abstract: Background The definitions of childhood asthma differ among epidemiological studies. We aimed to compare the diagnostic accuracy and agreement of previous asthma definitions and to evaluate questionnaire‐driven asthma definition patterns. Methods Data on 808 participants aged 7‐12 years from 20 schools were analyzed. Asthma definitions based on symptoms assessed by questionnaire, parent‐reported medical asthma diagnosis, current use of asthma medication, airway reversibility after bronchodilatation, and increa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
21
0

Year Published

2019
2019
2021
2021

Publication Types

Select...
9

Relationship

6
3

Authors

Journals

citations
Cited by 19 publications
(21 citation statements)
references
References 22 publications
0
21
0
Order By: Relevance
“…Asthma was defined using a gold standard definition based on a positive bronchodilation (BD) defined as at least 12% and over 200mL increase in FEV1 after inhaling 400 μg of salbutamol; or had self-reported medical diagnosis of asthma with symptoms (wheezing, dyspnea or dry cough) in the previous year [12]. Additionally, different asthma phenotypes were created based on classical definitions that involved several asthma features and traits [13]: i) allergic asthma, defined by positive skin prick tests (SPT); ii) eosinophilic asthma, defined by exhaled nitric oxide above 35 ppb; iii) obese asthma, defined by overweight or obesity; iv) persistent asthma, defined by current use of anti-asthma medication; v) symptomatic asthma, defined by current symptoms; vi) positive bronchodilation with asthma symptoms (BD+S+); vii) positive bronchodilation without asthma symptoms (BD+S-); and viii) negative bronchodilation with asthma symptoms (BD-S+).…”
Section: Methodsmentioning
confidence: 99%
“…Asthma was defined using a gold standard definition based on a positive bronchodilation (BD) defined as at least 12% and over 200mL increase in FEV1 after inhaling 400 μg of salbutamol; or had self-reported medical diagnosis of asthma with symptoms (wheezing, dyspnea or dry cough) in the previous year [12]. Additionally, different asthma phenotypes were created based on classical definitions that involved several asthma features and traits [13]: i) allergic asthma, defined by positive skin prick tests (SPT); ii) eosinophilic asthma, defined by exhaled nitric oxide above 35 ppb; iii) obese asthma, defined by overweight or obesity; iv) persistent asthma, defined by current use of anti-asthma medication; v) symptomatic asthma, defined by current symptoms; vi) positive bronchodilation with asthma symptoms (BD+S+); vii) positive bronchodilation without asthma symptoms (BD+S-); and viii) negative bronchodilation with asthma symptoms (BD-S+).…”
Section: Methodsmentioning
confidence: 99%
“…In fact, in the present study, among children with higher eNO ( n = 75), only 18 have asthma defined by self-reported medical diagnosis with reported symptoms (wheezing, dyspnea, or dry cough) occurring in the past 12 months or positive bronchodilation (data not shown). Moreover, our group previously showed that eNO had very low diagnostic accuracy for asthma [ 53 ]. Nonetheless, the mechanisms that led its production, either to be a mediator of cell damage or a mechanism of defense under pro-oxidant environments, are not completely understood [ 46 ].…”
Section: Discussionmentioning
confidence: 99%
“…However, compared to direct measures, self-reported methods may be able to represent the type of activity that is undertaken [47]. Although current asthma was not diagnosed by a physician, the used criteria in this study included a standardized operational definition of asthma supported by objective lung function measurements [48]. Another limitation of our study is the fact that food intake was evaluated using questionnaires, which can lead to bias.…”
Section: Discussionmentioning
confidence: 99%